Mathematical Reasoning and Self Regulated Learning According to Student’s Cognitive Stage - Gunawan Gunawan; Ambar Prawoto; Utari Sumarmo ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2019)
This study was a descriptive survey having a goal to examine attainment of student’s mathematical reasoning (MR) and  self regulated learning(SRL) according to  student’s cognitive stage. The survey   implicate  36 eleventh grade students of  17... years old,  test of logical thinking (TOLT), an essay  MR test,a  SRL scale. By using TOLT, the survey investigated  many students with 17 years old had not reached formal cognitive stage, namely 19 %  students at formal stage, 25 % students at transition stage, and  rest 56% students at concrete stage. In addition, survey invented that entirely students obtained MR at very low grade level, and according to student’s cognitive stage, formal students obtained higher grade MR than the grade of transisiton students and concrete students. Even if, those grades were still at low and very low level. Either entirely or based on student’s cognitive stage  there were no different grades on student’s SRL and those grade were fairly good level. SRL at fairly good grade level, transistion stage students attained  MR and SRL at medium grade Other finding, there was medium association between cognitive stage and MR, but therewere no association between cognitive stage and MR, and SRL and between MR and SRL. In general, these findings were, that in normal condition formal cgnitive stage will reach by students in 12 -13 years old, or in 13-14 years old, even in specific condition in 19 – 20 years old; and that formal students possess higher abilities than concrete students on completing HOT tasks such as MR tasks which needed formal operational thinking.